Case Study Of Strength And Calculation Of Remaining Service Life On Rig Equipment Using Pt Xyz's Finite Element Analysis - Satya Wicaksana; Deni Ferdian; Johny W. Soedarsono; Mirza Mahendra (Jurnal Indonesia Sosial Teknologi, 2023)
Indonesia is a country that has a variety of natural resources, one of which is oil and gas. In the process of drilling for petroleum, one of the equipment used is a Rig. Age factors can affect the performance of the rig system. Where a structure is depleted beyond ten per cent, then the contribution must be the element undergoing repair or replacement of the defective. The Depletion structure must be repaired. Before operating with new materials, return to the initial condition. Therefore, Regulation Number 32 of 2021, Safety Inspection of Installations and Equipment in Oil and Gas Business Activities, sets the remaining life limit for equipment service. The research method used in this paper refers to the strength of the Rig Tower member, which is calculated using applicable formulas and standards. The final step is a simulation performed using FAE MSC Nastran software. In the calculation, the loading cases of API Spec 4F are used, namely: 1. Max. Rated static hook load of 90.7 tnf (889,463.2 N) with 6 lines, 2. Wind speed of 60 knots with pipe setback. The calculation results can be concluded that the structure of PT XYZ's Rig tower is strong enough against the Maximum Static Hook Load of 889,463.2 N (6 lines), wind load of 60 Knots with pipe setback, rig up load and can last for 30.39 (thirty-thirty-nine hundredths) of years for fatigue, 24 (twenty-four) years for environmental corrosion (Upper Mast) and 20.56 (twenty-fifty-six hundredths) of a year for abrasion corrosion (Lower Mast).